The Strategic Role of MSMEs in Advancing a Sustainable and Resilient Global Economy - Marthanti, Amas Sari; Rosento, Rosento; Lahat, Mohammad Amas; Sabil, Sabil; Suratriadi, Panji; Adawia, Popon Rabia (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Through a systematic synthesis of recent international studies, this article conceptualizes the interconnection between digitalization, sustainability, and the resilience of small and medium-sized enterprises (SMEs), while also outlining prospective research directions related to inclusive and context-sensitive digital transformation models across varied business settings. Employing a systematic literature review (SLR) methodology aligned with PRISMA guidelines, the study critically evaluates contemporary scholarly publications to explore how digital technologies shape sustainable development trajectories and organizational robustness within SMEs. The analysis demonstrates that digital transformation plays a pivotal role in reinforcing SME competitiveness and adaptability, particularly within an environment characterized by globalization pressures and recurrent economic disruptions. More specifically, digital adoption enhances operational efficiency, enables the development of sustainability-driven business models, strengthens supply chain risk management, and promotes deeper customer engagement through improved responsiveness and interaction. Despite these advantages, the review also reveals persistent barriers, including constrained financial and technological resources, internal cultural resistance to change, and substantial deficiencies in digital competencies. Overall, this article offers a conceptual enrichment of existing literature while providing practical insights for business actors, policymakers, and other stakeholders in designing strategic initiatives aimed at reinforcing the long-term competitiveness and resilience of the SME sector.